English HUBUNGAN POLA MAKAN DENGAN KEJADIAN OBESITAS PADA TENAGA KESEHATAN DI PUSKESMAS - saleh, ismael (JURNAL BORNEO AKCAYA, 2020)
The prevalence of obesity is increasing both globally and nationally from year to year. It was supported by the results of a preliminary study that showed 38% of health workers in a health center were obese. The main factor of obesity was caused by unbalanced eating patterns, energy consumption, carbohydrates, fat and lack of physical activity. The study aimed to determine the factors of eating patterns associated with the incidence of obesity in health workers in the primary health center. The research design was Cross Sectional. The population in this study was 55 people. The samples were selected by purposive sampling they numbered 47 people. The results showed that the diet associated with obesity of puskesmas workers included more energy consumption (p = 0,000), consumption of more carbohydrates (p = 0.004), consumption of more fat (p = 0,000), insufficient of sleep (p = 0,000) and history genetic (p = 0.011). Unrelated variables were rush eating behavior (p = 0.707), sleep after eating (p = 0.870). Related to the results of this study, the puskesmas need to make consumption change behavior program for the health workers through education and nutrition counseling and to increase physical activity to health workers regulary. Keywords: Eating pattern, Obesity, health workers, puskesmas